A Review on Methods of Identifying and Counting Aedes Aegypti Larvae using Image Segmentation Technique - Mohamad Aqil Mohd Fuad; Mohd Ruddin Ab Ghani; Rozaimi Ghazali; Mohamad Fani Sulaima; Mohd Hafiz Jali; Tole Sutikno; Tarmizi Ahmad Izzuddin; Zanariah Jano (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
Aedes aegypti mosquitoes are a small slender fly insect that spreads the arbovirus from flavivirus vector through its sucking blood. An early detection of this species is very important because once these species turn into adult mosquitoes a population control becomes more complicated. Things become worse when difficult access places like water storage tank becomes one of the breeding favorite places for Aedes aegypti mosquitoes. Therefore, there is a need to help the field operator during the routine inspection for an automated identification and detection of Aedes aegypti larvae, especially at difficult access places. This paper reviews different methodologies that have been used by various researchers in identifying and counting Aedes aegypti. The objective of the review was to analyze the techniques and methods in identifying and counting the Aedes Aegypti larvae of various fields of study from 2008 and above by taking account their performance and accuracy. From the review, thresholding method was the most widely used with high accuracy in image segmentation followed by hidden Markov model, histogram correction and morphology operation region growing.